A qualitative exploration of the lived experiences of Body Dysmorphic Disorder - Brennan, Sarah N.; Rossell, Susan L.; Rehm, Imogen; Thomas, Neil; Castle, David J. (Frontiers in Psychiatry, 2023)
Body Dysmorphic Disorder (BDD) is characterised by an intense preoccupation with one or more perceived "defects" in physical appearance. Despite the distress and impairment associated with BDD, the disorder remains understudied and poorly understood. In particular, there are limited studies available which give voice to those with firsthand experiences of the disorder. A qualitative approach was employed to study lived experience of BDD. In-depth semi-structured interviews were conducted with twelve participants with BDD, aiming to understand their subjective experiences of the disorder. Data was analysed using Interpretative Phenomenological Analysis (IPA). The results identified three superordinate themes; (1) consumed by the disorder, (2) the flawed self, and (3) intolerance of uncertainty about appearance. The qualitative findings of this study are discussed in relation to current conceptual understandings of BDD, including the cognitive behavioural model.